PENERAPAN PROGRAM BOARDING SCHOOL TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMP MUHAMMADIYAH 1 BANJARNEGARA - Inung Nurlita; Rifqi Muntaqo; Hidayatu Munawaroh (Lembaga Pengembangan Kinerja Dosen, 2023)
The results showed that 1) The application of the boarding school program to the learning achievement of PAI at SMP Muhammadiyah Banjarnegara was carried out by the first teacher of the worship practice program, namely the midnight prayer in congregation, morning prayer and morning dhikr, rote deposit, congregational midday prayer, afternoon prayer, evening prayer, muroja'ah memorization, maghrib prayer, tadarus and evening prayer. Second, teaching the book, namely the program teaching the book, which proves that students can understand more deeply about the science of monotheism, worship, muamalah, and morals. The four programs for developing English and Arabic skills have been proven to be able to increase PAI learning achievement because more PAI material relates to the Al-Qur'an and Hadith so that mastery of Arabic is important. The learning achievement of Islamic boarding school students is relatively good, this can be seen from the acquisition of report cards which have a value above 80. 2) The obstacle to the application of the boarding school program on Islamic education learning achievement is the existence of scouting activities, the practice of midnight prayers and obligatory prayers which require supervision, low student participation and relatively weak student memorization. 3) Solutions to the constraints of implementing the boarding school program on Islamic education learning achievement, namely dormitory programs and activities carried out regularly, teachers providing assistance in worship, giving awards or rewards to students who are role models for other students, strengthening the physical and psychological aspects of students and the existence of support full of subject teachers and tahfidz teachers for the sake of creating hafidz as the school wants.